2011
DOI: 10.3390/sym3010054
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perception on the Distribution of Multiple Symmetries in Nature and Art

Abstract: Much is already known about single mirror symmetry, but multiple mirror symmetry is still understood poorly. In particular, perceptually, multiple symmetry does not seem to behave as suggested by the number of symmetry axes alone. Here, theoretical ideas on single symmetry perception and their extensions to multiple symmetry are discussed alongside empirical findings on multiple symmetry perception. The evidence suggests that, apart from the number of axes, also their relative orientation is perceptually relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 67 publications
(95 reference statements)
1
17
0
Order By: Relevance
“…However, there is also difficulty with this interpretation, due to the fact that there is not always a correspondence between preference and detection performance. In addition, while we found that preference increased with the tested number of axes, there may not be a monotonic relationship between goodness and the number of axes in multiple symmetric patterns [46].…”
Section: Theoretic Implicationsmentioning
confidence: 55%
“…However, there is also difficulty with this interpretation, due to the fact that there is not always a correspondence between preference and detection performance. In addition, while we found that preference increased with the tested number of axes, there may not be a monotonic relationship between goodness and the number of axes in multiple symmetric patterns [46].…”
Section: Theoretic Implicationsmentioning
confidence: 55%
“…The failure to recognize this crucial point has led to overly strong claims (see also Bowers & Davis, 2012a, 2012b. For instance, Chater (1996) claimed that the simplicity and likelihood principles in perception are equivalent, but this claim assumed implicitly -and incorrectly -that any Bayesian model automatically implies compliance with the Helmholtzian likelihood principle (van der Helm, 2000(van der Helm, , 2011a. This may be clarified further as follows.…”
Section: Bayesian Modelsmentioning
confidence: 99%
“…Hence, to determine if the Bayesian formulation of the simplicity principle complies with the likelihood principle, one should assess how close the latter 's objective probabilities pw and the former's artifical probabilities pa might be (van der Helm, 2000(van der Helm, , 2011a. This is discussed further in the next section, but notice that a proof of equivalence of the principles is out of the question, simply because the pw are unknown.…”
Section: Select the Hypothesis H That Maximizes Pa(h|d)=pa(h)*pa(d|h)mentioning
confidence: 99%
“…In fact, studies have shown that both female swallows [1] and finches [2] prefer symmetric males, and honey bees [3] can discriminate symmetry from non-symmetry. Such studies have suggested to some that symmetry in the visual world has played a causal role in the evolution of our visual systems and hence our sensitivity to symmetry, or vice versa [4].…”
Section: Introductionmentioning
confidence: 99%